INTRATUNNEL THE EFFECT OF ADMINISTRATION OF BONE MARROW MESENCHYMAL STEM CELLS (BM-MSCs) AND VASCULAR ENDOTHELIAL GROWTH FACTOR (VEGF) TENDON-BONE TO INTERFACE HISTOLOGICAL GRAFT ANTERIOR CRUCIATE LIGAMENT APPEARANCE AFTER RECONSTRUCTION IN RABBITS - abirama, atria (Stem Cell Research and Development Center, Universitas Airlangga, 2018)
The success of the Anterior Cruciate Ligament (ACL) reconstruction using a tendon graft is determined by integration in the bone tendon-graft interface on the bone tunnel. The use of stem cells and growth factors proved to accelerate the healing of the bone tendon-graft interface. The aim of this study was to inveestigate the difference of histology picture in the tendon-bone tunnel model after ACL reconstruction with intratunnel intravenous allogenic bone marrow mesenchymalstemcells (BM-MSCs) and intratunnel vascular endothelial growth factor (VEGF). This research used Post-Test Only Control Group design with 20 rabbits divided into treatment group and control group. Each group performed histologic image evaluation (thickness of collagen fiber or sharpey fiber) at week 3 and 6. Evaluation of histology overview at week 3 and week 6 showed a significantly thicker thickness of collagen fiber or sharpey fiber in treatment group compared with control group (p <0.05). Intravenous administration of BM-SCs and VEGF after ACL reconstruction can speed healing of the bone tunnel significantly from week 3 and 6. The study by Faridyan et al has concluded that intravenous BM-SCs + VEGF increased ultimate tension strength in the bone-tendon interface significantly. In this study, intravenous administration of BM-SCs and VEGF gave histologic images showing acceleration of bone tunnel healing.Keywords:Anterior cruciate ligament reconstruction, allogenic bone marrow mesenchymal stem cells, vascular endothelial growth factor, graft tunnel healing, and Sharpey fiber.